Macroeconomic Variables and Stock Market Returns: Panel Analysis from Selected ASEAN Countries - Jamaludin, Nurasyikin; Ismail, Shahnaz; Manaf, Syamimi Ab (International Journal of Economics and Financial Issues, 2017)
This paper aims to examine the effect of macroeconomic variables namely inflation, money supply, and exchange rate on both conventional and Islamic stock market returns in the three selected ASEAN countries (Singapore, Malaysia, Indonesia) by utilising monthly data over the period of January 2005 to December 2015. Applying the panel least square regression techniques, the results show that both stock market returns are significantly affected by the exchange rate and inflation rate. Money supply is found to be insignificant. The findings of this paper also conclude that inflation poses a greater effect and inversely related to the stock market returns. In this case, there is a need for amendment in monetary policy to ensure that inflation rate is set at a low level, since the results would be able to bring an impact to boost the capital market in the selected ASEAN countries. Keywords: macroeconomic variables, stock market returns, ASEAN JEL classifications: E03, E60, G10, G18, F62